INDICATORS OF SPECIFICITY OF CLIMATE: THE EXAMPLE OF PODGORICA (MONTENEGRO) - Dragan Burić; Radomir Ivanović; Milan Milenković (Zbornik Radova: Geografski institut "Jovan Cvijić", 2018)
Climatic indices complexly display the climate of a place, and certainly influence its more qualitative characterization. In this paper, the specificity of the climate is analyzed, such as the degree of continentality and aridity, in the example of the city of Podgorica. The climate was considered on the basis of the data for almost the entire instrument period (1951–2017). The results obtained for thermal continentality show that maritime influences are primary and predominant, but the influence of the continent is also significant. In a hygric sense, the climate of Podgorica is characterized as poorly arid to poorly humid with significant oscillations during the year. The warmer period of the year, especially the summer, has the characteristics of arid climate. The colder period of the year, especially from November to February, has the characteristics of humid and even perhumidic climate, while the transitional seasons show signs of semi-aridity and semi-humidity.